AN EVALUATION AND PROPOSAL ON THE MEASUREMENT NECESSITY FOR CONTROLLING INFLATION EXPECTATIONS OF DIFFERENT SEGMENTS IN TÜRKİYE (Third Sector Social Economic Review, 2023)
The concept of expectations, in economic terms, focuses on individuals' perceptions of future values of variables reflecting their anticipations of forthcoming economic conditions. Inflation expectations constitute a crucial determinant of economic behavior, financial decisions, and policy outcomes, while also serving as a pivotal variable monitored and guided by central banks to manage inflation. Although the Central Bank gauges inflation expectations for representatives of the real and financial sectors, as well as professionals in Türkiye, it does not assess inflation at the micro level for lower-income groups. Concentrating solely on one segment of the economy's inflation expectations may lead to indicator bias. This study provides essential insights for enhancing the effectiveness of economic policies by considering the relationship between inflation expectations and economic actors through diverse viewpoints. Evaluating the measurement of inflation expectations across various sectors is vital to comprehending their impacts on economic decision-making processes and formulating a more resilient monetary policy. Within this context, the study underscores that inflation expectations among farmers might diverge from those of other economic segments, necessitating a deeper understanding of the resulting implications for monetary policy. Furthermore, while discussing the importance and potential consequences of quantitatively presenting inflation expectations for different segments of society, such as farmers, the study reveals that obtaining farmers' inflation expectations as a time series can facilitate empirical testing of numerous hypotheses. In the study, the necessity of this measurement to maintain the price stability and rational expectations is explained by a literature review and intellectual dimension.
Keywords: Inflation Expectations; Rationality; Policy Efficiency; Monetary Policy; Central Bank